2014
DOI: 10.1586/14737159.2014.933075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostics clinical utility strategy: a six-part framework

Abstract: The clinical utility of a molecular test rises proportional to a favorable regulatory risk/benefit assessment, and clinical utility is the driver of payer coverage decisions. Although a great deal has been written about clinical utility, debates still center on its 'definition.' We argue that the definition (an impact on clinical outcomes) is self-evident, and improved communications should focus on sequential steps in building and proving an adequate level of confidence for the diagnostic test's clinical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The most frequently used formats are the key questions format (12 frameworks) [ 7 , 11 15 , 20 23 , 32 , 41 , 42 ], the card format (five frameworks) [ 8 – 10 , 16 19 , 24 , 25 ], and the checklist format (two frameworks) [ 30 , 38 ]. The other frameworks have a less structured format and resemble general manuals (Table 2 ) [ 26 – 29 , 31 , 33 – 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently used formats are the key questions format (12 frameworks) [ 7 , 11 15 , 20 23 , 32 , 41 , 42 ], the card format (five frameworks) [ 8 – 10 , 16 19 , 24 , 25 ], and the checklist format (two frameworks) [ 30 , 38 ]. The other frameworks have a less structured format and resemble general manuals (Table 2 ) [ 26 – 29 , 31 , 33 – 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This left a total of 20 studies that met our inclusion criteria and were subsequently abstracted. 5,7,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart is shown in Figure 1.…”
Section: First Stage: Targeted Systematic Literature Review and Identification Of The Components Of The Value Framework And Initial List mentioning
confidence: 99%
“…It builds on previous frameworks, including the United States Preventive Services Task Force approach for assessing preventive interventions (21); the Fryback–Thornbury hierarchy (22); the ACCE (Analytic Validity, Clinical Validity, Clinical Utility, and Ethical, Legal, and Social Implications) framework (23); the EGAPP (Evaluation of Genomic Applications in Practice and Prevention) standards (24); the Genetic testing Evidence Tracking Tool (GETT) (25); and the Frueh and Quin framework that aims to facilitate communication between test developers and health-technology evaluators (26). …”
Section: What Framework Should Guide Decision Making On the Use Of Bimentioning
confidence: 99%